Trypsiligase‐Catalyzed Labeling of Proteins on Living Cells. (15th January 2021) - Liebscher, Sandra; Mathea, Sebastian; Aumüller, Tobias; Pech, Andreas; Bordusa, Frank
Abstract: Fluorescent fusion proteins are powerful tools for studying biological processes in living cells, but universal application is limited due to the voluminous size of those tags, which might have an impact on the folding, localization or even the biological function of the target protein. The designed biocatalyst trypsiligase enables site‐directed linkage of small‐sized fluorescence dyes on the N terminus of integral target proteins located in the outer membrane of living cells through a stable native peptide bond. The function of the approach was tested by using the examples of covalent derivatization of the transmembrane proteins CD147 as well as the EGF receptor, both presented on human HeLa cells. Specific trypsiligase recognition of the site of linkage was mediated by the dipeptide sequence Arg‐His added to the proteins' native N termini, pointing outside the cell membrane. The labeling procedure takes only about 5 minutes, as demonstrated for couplings of the fluorescence dye tetramethyl rhodamine and the affinity label biotin as well. Abstract : Fluorescent fusion proteins : Herein, we describe a biocatalytic approach for the site‐specific bioconjugation of cell‐surface bound proteins by trypsiligase. The reactions are fast, irreversible, without side reactions and completely nontoxic to living cells. Importantly, recognition of the target membrane protein by trypsiligase only requires the introduction of a simple dipeptide sequence at its N terminus.